(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article highlights the key issues of intellectual capital management of enterprises. The existence of these problems has a systemic nature and their solution goes beyond the micro level of business. Intellectual capital, as an object of management, is not homogeneous. There are many related and adjacent concepts. The improvement of the terminology apparatus is based on the study of the essential characteristics of certain categories and the identification of the links between them. A separate problem is the structuring of intellectual capital. Within the three traditional constituents (human, organizational and consumer capital), the author presents his own specification of elements of intellectual capital. The problem of the economic evaluation of intellectual capital and its elements lies in the subjectivity of existing methods. Comparative analysis of evaluation methods, identifying their advantages and disadvantages for individual cases allows us to find the best way to evaluate. The author proposes solving the problem of methodology of intellectual capital management at the intersection of functional and process approaches to management. The obtained results have a theoretical character and are the basis for development of applied methods of management of intellectual capital of enterprises.